Berbagi Ilmu dan Menginspirasi “Saatnya Yang Muda Berkarya” - Irsyadi Zain; Jusmarni; Resti Riandi (Jurnal Mitra Pengabdian Farmasi, 2021)
This community service activity aims to provide enthusiasm and motivation to the younger generation about the importance of the younger generation to work for the nation, especially in the economic field. For this reason, the younger generation needs to do something positive that can be developed with creative ideas and innovations from the youth as the nation's successors, especially the Entrepreneurial Youth Community in the Riau region in the city of Pekanbaru. . This service method uses the method of sharing knowledge and experience of the Community Service team followed by a question and answer session from the audience. The method of sharing knowledge and experience is used to convey knowledge and experience in general about how to build a business or entrepreneurship, how to find creative ideas for a work and what to prepare and the steps in developing existing works. The question and answer method is used to complete things that have not been explained by the knowledge and experience above. In this sharing of knowledge and experience, it involved lecturers of the Management study program in collaboration with the owner of the Quantung coffee shop and the Riau Region Entrepreneurial Youth Community as the target subjects.